Five-year outcome of non-shunting and primary closure technique during carotid endarterectomy: a longitudinal cohort study - Aram Baram; Zana A. Mohammed; Sarwer Jamal Al-Bajalan; Fitoon Falah (Journal of International Medical Research, 2022)
Objective The long-term outcomes of primary carotid artery closure after carotid endarterectomy (CEA) have not been sufficiently studied. This prospective study was performed to analyze the 5-year outcomes of the non-shunting and primary arterial repair technique for CEA. Methods This study involved 150 patients who underwent CEA with the primary arterial closure technique without arterial shunting and completed 5 years of follow-up. Results The patients comprised 107 men and 43 women. The 30-day postoperative course was uneventful in 147 (98.0%) patients; however, cerebrovascular accidents occurred in 3 (2.0%) patients. With respect to the long-term results, most cases of restenosis at 5 years were <50%. Two patients developed asymptomatic total internal carotid artery occlusion. Eleven deaths occurred (mortality rate of 7.3%); one death (0.7%) occurred in the first 30 days. Conclusion Primary arteriotomy closure provides very good long-term patency. Routine use of patch closure is unnecessary.